Elevated serum malondialdehyde (MDA), insulin, follicle-stimulating hormone (FSH), luteinizing hormone (LH), and thyroid-stimulating hormone (TSH), and reduced antioxidant vitamins in polycystic ovarian syndrome patients - Abdullah A. Mahmud; Umme H. Anu; Kazi A. Foysal; Mahedi Hasan; Sazaul M. Sazib; Abdullah A. Ragib; Asad B. Taher; Md Shajjad Hossain; Mohammad S. Islam; Md Shohel Hossain; Talha B. Emran (Narra Sains Indonesia, 2022)
Elevated oxidative stress and hormonal imbalance have been suggested associate with polycystic ovarian syndromes (PCOS), a causal factor for unsuccessful pregnancy outcomes and other associated complications in women. The aim of this study was to compare the oxidative stress markers and different relevant hormone between pregnant women with and without PCOS. The levels of malondialdehyde (MDA), insulin, follicle-stimulating hormone (FSH), luteinizing hormone (LH), thyroid-stimulating hormone (TSH), vitamin A and vitamin C were measured in 80 pregnant women with PCOS and 80 healthy pregnancies. The mean MDA and insulin levels were significantly elevated in pregnant with PCOS compared to healthy controls (1.98±0.07 vs. 1.06±0.02 nmol/mL and 11.15±0.25 vs. 6.67±0.25 mIU/L, respectively with p<0.001 for both). Compared to healthy controls, the mean concentrations of FSH (3.65±0.16 vs. 1.75±0.10 IU/L) and LH (15.67±0.63 vs. 3.65±0.16 IU/L) were significantly higher in pregnant women with PCOS, p<0.001 for both comparisons. Similarly, the concentration of serum TSH was also higher in PCOS cases compared to controls (2.79±0.22 vs.2.34±0.06, p=0.048). In contrast, the levels of vitamin A and C were lower in PCOS cases compared to healthy pregnancy group, 0.45±0.01 vs. 1.05±0.01 and 0.26±0.01 vs. 0.53±0.02, respectively with p-values <0.001 for both comparations. In conclusion, in PCOS, serum MDA, insulin, FSH, LH and TSH levels elevated while the level of antioxidant vitamins lower compared to healthy pregnant women. Unusual hormonal imbalance and increase of oxidative stress markers during the pregnancy might important to establish the PCOS diagnosis.